Land use changes and ground dwelling beetle conservation in extensive grazing dehesa systems of north-west Spain - García-Tejero, Sergio; Taboada, Ángela; Tárrega, Reyes; Salgado, José M. (Biological Conservation, 2013)
Abstract Traditional management practiced over centuries in Mediterranean cultural landscapes has led to singular agrosilvopastoral ecosystems such as dehesas. Recent abandonment of dehesa management has resulted in shrub encroachment, habitat homogenisation and increased fire risk. Mechanical shrub cutting to decrease biomass load creates novel cleared dehesas with yet unknown consequences for the ecosystem function. We investigated the effects of these land use changes on ground dwelling beetles (carabids and staphylinids) as model organisms by comparing traditionally grazed, long-time abandoned and newly cleared dehesas. Land use changes affected beetle species composition by altering habitat structure (e.g., litter layer) and the availability of feeding resources. Grazed dehesas held the highest number of exclusive species and particular functional guilds of carabid seed eaters and staphylinid coprophiles, utilizing food resources related to the presence of grazing livestock (annual herbs and coprophagous insects). Beetle assemblages of abandoned dehesas, resembling those known from surrounding human disturbed oak forests, exhibited the lowest abundance and greatly differed from beetle assemblages of grazed dehesas. Shrub clearance after dehesa abandonment benefited opportunistic beetle predators feeding on decomposers associated with cutting slash left on the ground. The habitat structure and beetle species composition of cleared dehesas slightly approached those of grazed dehesas, therefore suggesting shrub cutting as a first step towards restoration of abandoned dehesas. However, since livestock grazing is an essential driver of ground dwelling beetle composition, it should be promoted after shrub cutting in cleared dehesas to restore the characteristic assemblages, species interactions and ecosystem function of grazed dehesas.
Keywords: Carabid and staphylinid assemblages; Functional guild of species; Land use abandonment; Oak savannah-like forest; Shrub encroachment; Traditional silvopastoral management

Abandonment and management in Spanish dehesa systems: Effects on soil features and plant species richness and composition - Tárrega, Reyes; Calvo, Leonor; Taboada, Ángela; García-Tejero, Sergio; Marcos, Elena (Forest Ecology and Management, 2009)
Quercus pyrenaica dehesas have been traditionally used as communal extensive grazing systems in the Leo´n province (NW Spain). In this region, recent abandonment of rural areas and the subsequent gradual decrease in livestock load have led to the invasion of shrubs in the understory, increasing the risk of fires. Indeed, even if there is no need of creating new pasturelands for livestock breeding, the remaining landowners keep on burning to clear these montane patches. Alternatively, the regional administration encourages shrub cutting as a better way of managing these areas and preserving the pasturelands. Our aim was to determine the effects of the dehesa abandonment and shrub cutting on plant species richness (annual herbs, perennial herbs and woody plants) and species composition, as well as on topsoil properties. For that, we compared three types of dehesas with differentmanagement regimes: (1) grazed dehesas (used at the present), (2) abandoned dehesas (more than 20 years without grazing) and (3) dehesas where shrub cutting was applied after abandonment (i.e. cleared dehesas). We selected three replicates or stands per dehesa type. The highest organic matter content (O.M.), total nitrogen (N) and available phosphorus (P) were found in cleared dehesas, while the lowest values corresponded to the grazed ones. Abandoned dehesas were characterized by the highest values for available calcium (Ca2+). No significant differences were detected regarding the vegetation richness values (S alpha, gamma or beta), although higher mean values of S alpha and gamma were found in grazed dehesas, and lower values in the cleared ones. Concerning the vegetation life forms, grazed dehesas held significantly greater species richness and cover of annual herbs, while abandoned dehesas had significantly higher woody species cover. Both grazed and abandoned dehesas harboured plant species (38 and 13 species, respectively),which were exclusively found in one dehesa type. Contrary to that, cleared dehesas scarcely had ‘‘exclusive’’ species. To conclude, our results indicated that shrub cutting alone (not followed by livestock grazing) may cause loss of plant species richness, suggesting that it is not the most appropriate management method to restore vegetation, except for reducing the risk of fire.
Keywords: Land use change; management; Oak dehesa; Quercus pyrenaica; Species richness; Topsoil; Understory composition